1992
DOI: 10.2307/1941462
|View full text |Cite
|
Sign up to set email alerts
|

Root Communication Mechanisms and Intracommunity Distributions of Two Mojave Desert Shrubs

Abstract: Experimental studies using root observation chambers to observe the effects of encounters between individual roots on root elongation rates have revealed that the interactions among roots of Ambrosia dumosa and Larrea tridentata are more complex than simple competition for a limiting resource. Larrea roots inhibited elongation of either Larrea or Ambrosia roots in their vicinity, and Ambrosia roots inhibited elongation of contacted roots on other Ambrosia plants only. The purpose of the study reported here was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
229
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(239 citation statements)
references
References 45 publications
10
229
0
Order By: Relevance
“…The second bioassay, referred to as the 'root proliferation' experiment, was conducted in root observation chambers (Mahall & Callaway, 1992) with the aim of determining the capability of L. sativum seedling roots to colonize the different litter types independently from the germination process. A further aim was to assess the cause of growth inhibition.…”
Section: Nutrient Immobilization and Phytotoxicitymentioning
confidence: 99%
“…The second bioassay, referred to as the 'root proliferation' experiment, was conducted in root observation chambers (Mahall & Callaway, 1992) with the aim of determining the capability of L. sativum seedling roots to colonize the different litter types independently from the germination process. A further aim was to assess the cause of growth inhibition.…”
Section: Nutrient Immobilization and Phytotoxicitymentioning
confidence: 99%
“…Is there any empirical evidence supporting these ideas? A study of desert shrubs in the Mojave desert revealed that Larrea tridentata (creosote bush) produces root allelochemicals that inhibit the root elongation of neighboring plants, both con specifics and of other species [Mahall and Callaway, 1992]. By virtue of this mechanism, Larrea individuals are able to have near exclusive access to the soil resources directly beneath their root system.…”
Section: W06d02mentioning
confidence: 99%
“…Studies of the water and carbon relations of Larrea do indicate that it is a species that has a strategy of very slow growth and remarkable drought resistance. The lifespan of a Larrea shrub can be longer than 100 years despite their very low stature, indicating extremely slow growth [Mahall and Callaway, 1992].…”
Section: W06d02mentioning
confidence: 99%
“…The C cycle in desert ecosystems cannot be ignored in the global C cycle (Austin, 2011;Poulter et al, 2014). R s represents the second largest C flux between ecosystems and the atmosphere (Raich and Schlesinger, 1992;Raich et al, 2002), and exhibits high spatial variation in desert ecosystems (Mahall et al, 1992;Gold et al, 1995;Xie et al, 2001). In addition, active, semi-active aeolian, and fixed sand dunes are the primary features of desert landscapes.…”
Section: Introductionmentioning
confidence: 99%